Effect of tillage and integrated nutrient management practices on greengram (Vigna radiata) crop - TOMER, RAVINDRA; KUMAR, SANJEEV; KUMAR, RAHUL; RATHI, NEELMANI; BHOI, SUBHRASURAJITA (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during rainy season of 2015 and 2016 at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur with the objective to evaluate the effects of different tillage and integrated nutrient management (INM) practices on performance of greengram [Vigna radiata (L.) Wilczek] under greengram + sesame intercropping system. The experiment was laid out in a split-plot design with four tillage practices, viz. conventional tillage (CT), deep tillage (DT), CT + vegetative mulch and DT + vegetative mulch as main plots, and six INM practices, viz. 20-60-40 N-P2O5-K2O kg/ha, 30-60-40 N-P2O5-K2O kg/ha, 20-60-40 N-P2O5-K2O kg/ha + Rhizobium (soil inoculation), 20-60-40 N-P2O5-K2O kg/ha + Rhizobium + phosphorus solubilizing bacteria (PSB), 30-60-40 N-P2O5-K2O kg/ha + Rhizobium and 30-60-40 N-P2O5-K2O kg/ha + Rhizobium + PSB as sub plots with three replications. The DT + vegetative mulch resulted in significantly higher leaf area index (3.10), crop dry matter (10.10 g/plant), seed yield (9.02 q/ha) and net returns (37314.5 INR/ha) with 4.03%, 3.17%, 24.24% and 43% increment over CT, respectively. Among the INM treatments, the 30-60-40 N-P2O5-K2O kg/ha and Rhizobium + PSB resulted in highest leaf area index (3.09), crop dry matter (10.09 g/plant), seed yield (9.14 q/ha), net returns (33346.5 INR/ha), and nitrogen (17.67 kg/ha) and phosphorus (9.31 kg/ha) uptake by seed with mean 3.18%, 2.91%, 21.32%, 43.70%, 27.68% and 34.65% increase over sole application of chemical fertilizers.